Meningkatkan Kreativitas Belajar Siswa Menggunakan Model Pembelajaran Project Based Learning pada Mata Pelajaran IPA di Kelas V SD Negeri 34/I Teratai - Fatmawati Fatmawati; Gusnia Rindiani; Natasha Oktaviany; Syahrial Syahrial; Silvina Noviyanti (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The purpose of this study was to increase student learning creativity in science subjects by using a project based learning model in class V SD Negeri 34/I Teratai. This research is a Classroom Action Research (CAR). Where each cycle includes planning, implementation, observation and reflection carried out in 2 cycles. Conducted in class V at SD Negeri 34/I Teratai. The results of this study indicate that the application of the project-based learning model has a positive impact on increasing student learning creativity. Increased creativity in each indicator: for indicator 1 there was an increase in 12 students in the very good category, indicator 2 an increase in 6 students in the very good category, indicator 3 an increase in 11 students in the very good category, indicator 4 an increase in 3 students in the category very good, and indicator 5 there is an increase in 3 students in the very good category. The percentage increase in each cycle is: the first cycle of the first meeting the percentage obtained 59.4% increased in the second meeting to 66.25%, in the second cycle the first meeting experienced a percentage increase of 72.92% and the second meeting increased to 81.8%. The conclusion obtained from the results of this study is the use of a project based learning model in which the steps are (1) determining basic questions, (2) designing project plans, (3) developing schedules, (4) monitoring students and project progress, ( 5) testing the results and presentation or publication of project results, and (6) evaluating the process of project results, can increase student learning creativity in science subjects in class V SD Negeri 34/I Teratai.